PROSES PEMBUKTIAN SEORANG ANAK LUAR KAWIN TERHADAP AYAH BIOLOGISNYA MELALUI TES DNA - Budi Kusuma, Sanny; Wairocana, I Gusti Ngurah (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
This paper titled "A Verification Process Children Born of Unregistered Marriage to her Biological Father by DNA Test" in order to know the law enforcement of children prove process to the biological father by DNA test and what are the consequences for a man who proved to be the biological father of a children born of unregistered marriage because it is not fair and right if our law let the man which is a biological father from a child who was born of unregistered marriage free. The research that used is normative legal research. Conclusions from the study are a verification process an children born of unregistered to the biological father by DNA tests have the law enforcement because it is done by experts and reflects the rule of law because the samples obtained the DNA test will not change throughout one’s life, and the consequence is the man who proved to be the biological father of the illegitimate child should be admitted and made Children Acknowledgement Act and Children Legalization Act to give bond as well as the force of law in the process of implementation of the demands of the rights and obligations of the legal relationship between illegitimate child with her biological parents, especially father.
Keywords: DNA test, children born of unregistered marriage, the biological father